Antecedents of financial practice for the success of small and medium enterprises (SMEs) : an empirical study in Malaysia - Azam, S.M. Ferdous (2015)
The world metaphorically has turned flat for the onslaught of globalization. While it has blurred the geographical divides, it has as well, as its corollary, spawned fierce competition among the enterprises in the marketplace. The competitive trade atmosphere has furnished the contemporary business industry intensely over its rivals and its ability to cope with multiple challenges to be successful, especially in terms of financial means. Although the Small and Medium Enterprises (SMEs) are considered as the backbone of economic growth of a country, however SMEs in Malaysia are noted with dismay due to unexpected business failures. Despite the fact that many scholarly works have been conducted in Malaysia, nevertheless, the strong influence of the antecedents of financial practice such as Financial Knowledge (FK) and Financial Behaviour (FB) toward Financial Practice (FP) as well as Business Success (BS) are yet to be realized pertinently. For that reason, the current study emphasizes a variety of detailed theoretical perspectives as well as the empirical foundations for achieving the research objectives. In fact, these theoretical and empirical platforms make the research feasible in the areas of Financial Knowledge (FK), Financial Behaviour (FB), Financial Practice (FP) and Business Success (BS) of Malaysian SMEs. The research method of this study is 'survey method' and the unit of analysis is the individual respondent consisting business owners and managers from various SMEs in Selangor and the greater Kuala Lumpur region. Although a suitable sample of 63 business owners and managers of different SMEs were selected for the pilot study, later on, a sample of 302 data was considered as the final sample size for the current study. Since this is a quantitative research, so the primary empirical findings are reported using SPSS (Version 18.0), and then detailed out various investigations using AMOS (Version 16.0) software for executing the suitable Structural Equation Modelling (SEM) analyses. Prior to conducting SEM, Exploratory Factor Analysis (EFA) is performed to scrutinize the underlying dimensions of Financial Knowledge (FK), Financial Behaviour (FB), Financial Practice (FP) and Business Success (BS). Subsequently, the reliability analysis is checked via Cronbach's alpha coefficient of the four extracted factors for the purpose of ensuring the internal consistency. The results indicate that, although Financial Knowledge (FK) is positively related to the Financial Practice (FP) in Malaysian SMEs, but it is not directly related to the Business Success (BS). A similar phenomenon is observed in the Financial Behaviour (FB), which is positively related to the Financial Practice (FP) but not to the Business Success (BS) for the SMEs in Malaysia. Apart from these, the Financial Practice (FP) is found assertively allied to the Business Success (BS) while Financial Practice (FP) plays the mediating roles in the Financial Knowledge (FK) and Financial Behaviour (FB) toward Business Success (BS) in Malaysia. However, a reciprocal relationship is observed justifiably between Financial Knowledge (FK) and Financial Behaviour (FB). With these findings, the current study can fulfill the research objectives assembled in the initial chapter. Finally, this research will help to identify the requirements and solutions for finding out the policy to strengthen the enterprise and maximize the productivity and sustainable development.